The Gen Z Activism in Nepal: A New Social Movement Perspective - Pun Magar, Deepak (Bagiswori Journal, 2026)
A social movement is an organized and collective effort by people aimed at bringing about or resisting social, political and cultural changes. It is characterized by a shared purpose, sustained collective action and the objective of influencing society and public policies. This manuscript analyzes the emergence of the Gen Z activism in Nepal from sociological perspective of new social movement theory. The main objective of the study is to examines the nature, ideological basis, organizational structure and social impact of the Gen Z movement. The research adopts a qualitative and descriptive design based on secondary sources, including sociological theories, academic articles, policy reports and published materials on digital activisms. The study justifies the use of secondary data by emphasizing the exploratory nature of emerging Gen Z movement, where primary data remains limited and fragmented. Theoretical frameworks such as new social movement theory, the concept of generational consciousness an digital sociology are employed to interprets the phenomenon. The findings reveal that Gen Z youth in Nepal are increasingly challenging traditional party-centric politics by promoting issues such as identity, good governance, social justice and accountability through digital platforms. The non-leadership and network-based structures of these movements denotes a decentralized and flexible form of mobilization, which enhances inclusivity but may weaken long-term organizational sustainability and institutional transformation. It offers new insight by linking Gen activism with broader transformations in democratic participation and digital political engagement in Nepal. However, the study is limited by its reliance on secondary data and the lack of empirical field-based evidence. Overall, it provides a theoretical foundation for future research and contributes to understanding Gen Z movements as a significant dimension of contemporary social change and democratic practice in Nepal.